TATALAKSANA RADIOTERAPI EKSTERNA PADA KANKER PAYUDARA DENGAN TEKNIK SIMULTANEOUS INTEGRATED BOOSTER (SIB) DI UNIT RADIOTERAPI INSTALASI RADIOLOGI RS KEN SARAS KABUPATEN SEMARANG - Ardani Ardani; Edy Susanto; Nanang Sulaksono; Sri Mulyati (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: Radiotherapy is a cancer treatment method using ionizing radiation. The SIB technique is a technique of providing additional radiation together with the administration of primary radiation. At Kensaras Hospital, booster treatment performed simultaneously with the administration of primary radiation or known as SIB is carried out using the IMRT technique or also known as the SIB IMRT technique. whereas according to Susworo, irradiation techniques on breast cancer are not recommended using the IMRT technique, but should use the FIF technique. The purpose of this study was to determine the governance of radiotherapy and the reasons for choosing the SIB technique.Methods: This type of research is qualitative with a case study approach. Data collection was carried out in December 2018 until May 2019 at Ken Saras Hospital. Result: The results showed that the SIB technique had several advantages, among others: better radiation conformity and able to minimize OAR doses. This is proven by obtaining doses which mostly meet ICRU standards. While for OAR doses it also meets quantec tolerance standards, except the right lung at a dose of 2000 cGy the volume exceeds 30%, which is equal to 34.55%. But the dosage according to the doctor's consideration is still said to be safe. Conclutions: The external radiotheraphy procedure including consulting a doctor, taking CT Simulator data, TPS, verification and treatment. Strengths of the SIB technique: Better irradiation conformity, suppressing OAR doses, reducing toxicity to the skin, only requiring one planning and allowing dose calculation in one planning